Cellular responses to genome mistranslation - Costa, Tatiana Lima de Vilhena Magalhães (2012)
Low level protein synthesis errors can have profound effects on normal cell physiology and disease development, namely neurodegeneration, cancer and aging. The biology of errors introduced into proteins during mRNA translation, herein referred as mistranslation, is not yet fully understood. In order to shed new light into this biological phenomenon, we have engineered constitutive codon misreading in S. cerevisiae, using a mutant tRNA that misreads leucine CUG codons as serine, representing a 240 fold increase in mRNA translational error relative to typical physiological error (0.0001%). Our studies show that mistranslation induces autophagic activity, increases accumulation of insoluble proteins, production of reactive oxygen species, and morphological disruption of the mitochondrial network. Mistranslation also up-regulates the expression of the longevity gene PNC1, which is a regulator of Sir2p deacetylase activity. We show here that both PNC1 and SIR2 are involved in the regulation of autophagy induced by mistranslation, but not by starvation-induced autophagy. Mistranslation leads to P-body but not stress-granule assembly, down-regulates the expression of ribosomal protein genes and increases slightly the selective degradation of ribosomes (ribophagy). The study also indicates that yeast cells are much more resistant to mistranslation than expected and highlights the importance of autophagy in the cellular response to mistranslation. Morpho-functional alterations of the mitochondrial network are the most visible phenotype of mistranslation. Since most of the basic cellular processes are conserved between yeast and humans, this study reinforces the importance of yeast as a model system to study mistranslation and suggests that oxidative stress and accumulation of misfolded proteins arising from aberrant protein synthesis are important causes of the cellular degeneration observed in human diseases associated to mRNA mistranslation.